Impact of disease-management programs on metabolic control in patients with type 1 diabetes mellitus: A cohort study in Shantou, China. Issue 52 (December 2016) - Lin, Kun; Yang, Xiaoping; Wu, Yixi; Chen, Shuru; Yin, Guoshu; Zhan, Jianjun; Lin, Chujia; Xu, Wencan; Chen, Yongsong; Lin, Dan; Xie, Peiwen; Fang, Yishan; et al.
Abstract : Abstract: The aim of this study is to evaluate the effect of diabetes disease management program (DMP) on glycemic control in type 1 diabetes mellitus (T1DM) patients in Shantou China. A sample of 240 participants recruited from 3C study Shantou subgroup was followed up in DMP for 3 years. The DMP provided self-management education, individualized therapy plan, diabetes complications screening, and laboratory examination periodical according to clinical practice guidelines. Primary outcomes were changes in hemoglobin A1C (HbA1c). Two hundred one of the participants completed the follow-up. There was a significant decrease in the HbA1c levels after DMP implemented. The mean (± SD) pre- and post-intervention HbA1c levels were 10.26% ± 3.30% and 8.57% ± 1.57% respectively with a P value <0.001. General linear mixed model analyse demonstrated that changes in glycemic control were associated with insulin treatment regimen, frequency of Self-Monitoring of Blood Glucose (SMBG), diabetes diet adherence, physical activity, and duration of diabetes. DMP helped to improve glycemic control and should be general implemented in China's T1DM. Individuals with basal-bolus regimen (multiple daily injections or pump therapy), more frequency of SMBG, following a diabetes diet, more physical activity, shorter diabetes duration may derive greater benefits from DMP.